Politeknik Penerbangan Palembang Model Safe Qurban: Integrasi Filantropi Kolektif dan Budaya Keselamatan Penerbangan dalam Kegiatan Pengabdian kepada Masyarakat di Politeknik Penerbangan Palembang - Anton Abdullah; Ahmad Hariri; Mohammad Syukri Pesilette; Sunardi Sunardi; Dwi Candra Yuniar; Wildan Nugraha; Sutiyo; Dwi Cahyono; Direstu Amalia; Zusnita Hermala; Vania Nadhifa Azzara; Fadhilla Nina Rizkyanti; Yudita Nirmala Kartikasari; Minulya Eska Nugraha; Astri Puspita Kesuma (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2026)
Qurban is not only a religious ritual with spiritual significance but also an instrument of Islamic philanthropy that strengthens social solidarity and community welfare. At the same time, qurban activities involve various operational hazards that require the implementation of a safety culture. This community service program aimed to implement the Safe Qurban model by integrating collective philanthropy and aviation safety culture into the organization of Qurban 1447 H at Baitul Ilmi Mosque, Palembang Aviation Polytechnic. The program was carried out through several stages, including fundraising through the Shodaqoh Qurban Program, hazard identification, safety planning, qurban implementation, benefit distribution, and program evaluation. The results demonstrated that collective philanthropy successfully broadened community participation in qurban activities through collaborative contributions while fostering social solidarity, empathy, and mutual assistance. The application of safety culture was reflected in hazard identification, risk control, safety communication, clear task allocation, and emergency preparedness throughout the implementation process. The integration of these two approaches generated broader social benefits while simultaneously enhancing safety awareness among all participants. The program resulted in the development of the Safe Qurban model as an innovative community service approach that combines the values of Islamic philanthropy with safety culture practices adapted from the aviation sector. This model has the potential to be replicated in other social and community-based activities involving multiple stakeholders and operational risks. Keywords: aviation safety; collective philanthropy; community service; qurban; safety culture.